Indoor Radon measurements in dwellings in four districts of Al-Rusafa side – Baghdad - Amin, S A.; Al-Nuzal, S M. D.; Lami, M H. M.; Sami, S (Sulaimani Journal for Pure and Applied Sciences, 2015)
Indoor radon level measurements were carried out in 36 dwellings in Al-Rusafa side of Baghdad, using CR-39 solid state nuclear track detectors. The measurements were performed during spring 2013 (March, April and May) for a period of 90 days using a total of 120 dosimeters. The dosimeters were distributed in 4 districts in Al-Rusafa side (Rusafa, Adhamia, 9 Nissan and Karrada) and installed in living rooms, bedrooms and kitchens of each house, selected randomly in the investigated area. The average indoor radon concentration in Al-Rusafa dwellings was found with mean values of 13.9 Bqm-3. Annual effective dose and annual equivalent dose that Al-Rusafa inhabitants exposed to were 346.5µSvy-1 and 8.31mSvy-1, respectively. The mean values of radon concentration levels in bedrooms, kitchens and living rooms are 14.3, 15.0 and 14.5 Bqm-3 respectively. The results show that radon concentration levels in the investigated dwellings are far below 100 Bqm-3 as recommended by ICRP and WHO.
Keywords: indoor radon; passive dosimeter; dwellings CR39 SSNTD effective dose; Baghdad; AlRusafa side